2021
DOI: 10.3390/genes12020308
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of Astrocyte Elevated Gene-1/Metadherin (AEG-1/MTDH) in Cancer Clinicopathology: A Review

Abstract: Since its initial cloning in 2002, a plethora of studies in a vast number of cancer indications, has strongly established AEG-1 as a bona fide oncogene. In all types of cancer cells, overexpression and knockdown studies have demonstrated that AEG-1 performs a seminal role in regulating proliferation, invasion, angiogenesis, metastasis and chemoresistance, the defining cancer hallmarks, by a variety of mechanisms, including protein-protein interactions activating diverse oncogenic pathways, RNA-binding promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…Similarly, AEG-1 protein expression was analyzed in this study by IHC which showed overexpression of AEG-1 protein in primary CRC tissues compared to normal tissues [2]. AEG-1 might serve as a prognostic marker in CRC as all studies exhibited that level of AEG-1 increases with CRC progression and negatively correlate with overall survival [108]. In HCC, IHC analysis of 323 patients exhibited significant AEG-1 overexpression in 54.2% of the patients.…”
Section: Overview On Clinicopathological Significance Of Aeg-1 In Different Cancer Typesmentioning
confidence: 69%
“…Similarly, AEG-1 protein expression was analyzed in this study by IHC which showed overexpression of AEG-1 protein in primary CRC tissues compared to normal tissues [2]. AEG-1 might serve as a prognostic marker in CRC as all studies exhibited that level of AEG-1 increases with CRC progression and negatively correlate with overall survival [108]. In HCC, IHC analysis of 323 patients exhibited significant AEG-1 overexpression in 54.2% of the patients.…”
Section: Overview On Clinicopathological Significance Of Aeg-1 In Different Cancer Typesmentioning
confidence: 69%
“…Furthermore, our findings showed that MTDH, which is a type of scaffold protein, was regulated by miR-21-3p. MTDH is reported to participate in many key oncogenic pathways, including the Wnt signaling pathway by interacting with related proteins (Khan and Sarkar, 2021). The relationship between Wnt signaling and intestinal barrier dysfunction is complex and has never been truly determined.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling further promotes the EMT process, whilst suppressing autophagy. The TGF-β2/RSmads signaling pathway induced autophagy in gliomas, and has been reported to take place through AEG-1/MTDH activation [ 41 ], identified as a prominent oncogene [ 42 ]. Autophagy is essential in TGF-β-induced glioblastoma, whilst TGF-β is one of the most noticeable drivers of EMT, emphasizing the importance of the autophagy/TGF-β/EMT pathway as a therapeutic target for glioblastoma.…”
Section: Drivers Of Emt In Glioblastomamentioning
confidence: 99%